Impacts of Source of Health Funding on Child, Infant, Neonatal and Maternal Mortality in sub-Saharan African Countries - Clancy, Amy Kathleen (Curtin University, 2020)
This work analyzed the impact of sources of health and child health expenditure on health outcomes by analyzing existing data in sub-Saharan African countries between 2000 and 2014. Development assistance for health (DAH) as a percentage of total health expenditure was associated with greater improvements in child health outcomes than government expenditure on health (GEH) but neither DAH or GEH improved maternal health outcomes.